Countering Stereotypes: Job, Disability, and Human Dignity - Claassens, L. Juliana M. (Journal of religion, disability & health, 2013)
In the Book of Job, one finds a classic example of a person moving from able-bodied privilege to disability by means of a debilitating disease. This series of tragedies causes Job to become an outcast, alienated from his family and friends, and relegated to the outskirts of society. Throughout the Book of Job, one encounters some of the religious stereotypes regarding suffering, disease, and disability common to the Hebrew Bible, which relate to the many stereotypes and misguided perspectives that people with disabilities in today's society have to face—religion and theology quite often playing a negative role in transmitting and sustaining such harmful views. In the Book of Job, however, one also sees glimpses of a counter narrative that moves toward a new kind of speech regarding disability and theology, particularly with regard to what it means to be human. These glimpses of an alternative way of speaking about theology and disability serve as encouragement in our own journey to find different a kind of (theological) speech rooted in values such as human dignity, inclusion, and hospitality.